2017
DOI: 10.1080/17470218.2016.1276944
|View full text |Cite
|
Sign up to set email alerts
|

Physical Similarity or Numerical Representation Counts in Same–Different, Numerical Comparison, Physical Comparison, and Priming Tasks?

Abstract: Recent studies have highlighted the fact that some tasks used to study symbolic number representations are confounded by judgments about physical similarity. Here, we investigated whether the contribution of physical similarity and numerical representation differed in the often-used symbolic same-different, numerical comparison, physical comparison, and priming tasks. Experiment 1 showed that subjective physical similarity was the best predictor of participants' performance in the same-different task, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Although Model 1g can accommodate the present data, we may ask why effects of numerical distance arose here, when similar effects have not been present in other digit identity tasks when physical similarity was taken into account Cohen (2009;see also García-Orza et al, 2012, andZhang et al, 2018). This appears surprising, given that digit identification was the basic task in Cohen's (2009) earlier study, as it was here.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although Model 1g can accommodate the present data, we may ask why effects of numerical distance arose here, when similar effects have not been present in other digit identity tasks when physical similarity was taken into account Cohen (2009;see also García-Orza et al, 2012, andZhang et al, 2018). This appears surprising, given that digit identification was the basic task in Cohen's (2009) earlier study, as it was here.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, if one is presented with the sounds "fīv," it is possible to access the corresponding quantity demanded by a mental arithmetic problem. However, cases are beginning to emerge in which task performance does not depend on such cross-talk (Cohen, 2009;García-Orza et al, 2012;Zhang et al, 2018), as well as cases in which the operation of a processor is revealed even though successful task completion does not demand it (as in the experiments here). Such demonstrations should be considered against other cases in which effects are clearly context-dependent and emerge only as a consequence of the task constraints (see, e.g., Campbell, 2011;Cohen & Dehaene, 1995).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Such a pattern of results clearly emphasizes the fact that the physical characteristics of the numerical stimuli cannot be ignored in accounting for performance across a range of numerical tasks. Indeed, such a conclusion has now extensive support in the literature (see Cohen, 2009Cohen, , 2010Cohen & Quinlan, 2016;Defever, Sasanguie, Vandewaetere, & Reynvoet, 2012;Garciá-Orza, Perea, Mallouh, & Carreiras, 2012;Lin & Göbel, 2019;Wong & Szücs, 2013;Zhang, Xin, Feng, Chen, & Szücs, 2018).…”
Section: Introductionmentioning
confidence: 89%